Mixed‐monolayer of N‐hydroxysuccinimide‐terminated cross‐linker and short alkanethiol to improve the efficiency of biomolecule binding for biosensing. (15th July 2018) - Ataman Sadık, Demet; Eksi‐Kocak, Haslet; Ertaş, Gülay; Boyacı, İsmail Hakkı and Mutlu, Mehmet
Abstract : The goal of this study was to use a novel surface chemistry for modifying gold surfaces to decrease the steric hindrance, minimize the nonspecific bindings while providing directed immobilization of proteins for advancing the transducer property and to provide a biosensing platform for surface plasmon resonance (SPR) applications. Mixed self‐assembled monolayers (mSAMs) were prepared using 3, 3′‐Dithiodipropionic acid di (N‐hydroxysuccinimide ester) (DSP) and 6‐mercapto‐1‐hexanol (MCH) and the selected model proteins bovine serum albumin (BSA) and lysozyme were tested for binding efficiency. First, binding of these two proteins at constant concentration to different DSP:MCH mSAMs were compared to deduce the best molar ratio for forming mSAM using a continuous flow system coupled to SPR. Coincidently the maximum protein binding DSP:MCH mSAM were the same for both proteins. The change in Response Unit (∆RU) signal due to protein binding between DSP SAM and maximum protein binding DSP:MCH mSAM for lysozyme binding was more in comparison to BSA binding. Second, the effect of BSA and lysozyme concentration on binding efficiency to maximum protein binding DSP:MCH mSAM were compared and discussed. Lysozyme and BSA were shown to reach saturations on the same monolayer at concentrations of 5.7x10 −5 and 8.96x10 −6 [M] respectively, hence the molar ratio for limit concentrations is 6:1. The DSP SAM, MCH SAM, and DSP:MCH mSAMs where maximum and minimum protein binding occurs were also characterized with XPS and Attenuated total reflectance‐Fourier transform infrared (ATR‐FTIR) spectroscopy. Blank gold surface, maximum protein binding DSP:MCH mSAM and BSA immobilized DSP:MCH mSAM on gold surface were also investigated utilizing tapping mode AFM.